Acyl-homoserine lactone-based quorum sensing and quorum quenching hold promise to determine the performance of biological wastewater treatments: An overview. (August 2016) - Huang, Jinhui; Shi, Yahui; Zeng, Guangming; Gu, Yanling; Chen, Guiqiu; Shi, Lixiu; Hu, Yi; Tang, Bi; Zhou, Jianxin
Abstract: Quorum sensing (QS) is a communication process between cells, in which bacteria secrete and sense the specific chemicals, and regulate gene expression in response to population density. Quorum quenching (QQ) blocks QS system, and inhibits gene expression mediating bacterial behaviors. Given the extensive research of acyl-homoserine lactone (AHL) signals, existences and effects of AHL-based QS and QQ in biological wastewater treatments are being subject to high concern. This review summarizes AHL structure, synthesis mode, degradation mechanisms, analytical methods, environmental factors, AHL-based QS and QQ mechanisms. The existences and roles of AHL-based QS and QQ in biomembrane processes, activated sludge processes and membrane bioreactors are summarized and discussed, and corresponding exogenous regulation strategy by selective enhancement of AHL-based QS or QQ coexisting in biological wastewater treatments is suggested. Such strategies including the addition of AHL signals, AHL-producing bacteria as well as quorum quenching enzyme or bacteria can effectively improve wastewater treatment performance without killing or limiting bacterial survival and growth. This review will present the theoretical and practical cognition for bacterial AHL-based QS and QQ, suggest the feasibility of exogenous regulation strategies in biological wastewater treatments, and provide useful information to scientists and engineers who work in this field. Highlights: Endogenous AHL-based QS and QQ are coexisting in biological wastewater treatments. Exogenous regulation by selective enhancement of AHL-based QS or QQ is proposed. Exogenous addition of AHLs or AHL-producing bacteria enhances sludge performance. Exogenous AHL-based QQ effectively improves membrane flux in MBRs.